Genetic engineering of novel super long-acting Exendin-4 chimeric protein for effective treatment of metabolic and cognitive complications of obesity. (October 2020) - Lee, Jong Youl; Park, Taehoon; Hong, Eunmi; Amatya, Reeju; Park, Kyung-Ah; Park, Young-Hoon; Min, Kyoung Ah; Jin, Minki; Lee, Sumi; Hwang, Seungmi; Roh, Gu Seob; Shin, Meong Cheol
Abstract: A common bottleneck challenge for many therapeutic proteins lies in their short plasma half-lives, which often makes the treatment far less compliant or even disables achieving sufficient therapeutic efficacy. To address this problem, we introduce a novel drug delivery strategy based on the genetic fusion of an albumin binding domain (ABD) and an anti-neonatal Fc receptor (FcRn) affibody (AFF) to therapeutic proteins. This ABD-AFF fusion strategy can provide a synergistic effect on extending the plasma residence time by, on one hand, preventing the rapid glomerular filtration via ABD-mediated albumin binding and, on the other hand, increasing the efficiency of FcRn-mediated recycling by AFF-mediated high-affinity binding to the FcRn. In this research, we explored the feasibility of applying the ABD-AFF fusion strategy to exendin-4 (EX), a clinically available anti-diabetic peptide possessing a short plasma half-life. The EX-ABD-AFF produced from the E. coli displayed a remarkably (241-fold) longer plasma half-life than the SUMO tagged-EX (SUMO-EX) (0.7 h) in mice. Furthermore, in high-fat diet (HFD)-fed obese mice model, the EX-ABD-AFF could provide significant hypoglycemic effects for over 12 days, accompanied by a reduction of body weight. In the long-term study, the EX-ABD-AFF could significantly reverse the obesity-related metabolic complications (hyperglycemia, hyperlipidemia, and hepatic steatosis) and, moreover, improve cognitive deficits. Overall, this study demonstrated that the ABD-AFF fusion could be an effective strategy to greatly increase the plasma half-lives of therapeutic proteins and thus markedly improve their druggability. Graphical abstract: Image 1 Highlights: The first report of an exendin-4 fusion protein exploiting a high affinity anti-FcRn affibody. Maximizing the efficiency of FcRn-mediated recycling allows a remarkably long plasma half-life of 7 days. Super-long lasting exendin-4 fusion protein elicits extended hypoglycemic effects over 12 days. Exendin-4 fusion protein is also effective for metabolic and cognitive complications of obesity.